The Touchscreen‐Based Trial‐Unique, Nonmatching‐To‐Location (TUNL) Task as a Measure of Working Memory and Pattern Separation in Rats and Mice. Issue 9 (27th September 2021) - Barnard, Ilne L.; Onofrychuk, Timothy J.; McElroy, Dan L.; Howland, John G.
Abstract: The TUNL task is an automated touchscreen task used to evaluate the cognitive processes involved in working memory (WM) and spatial pattern separation in rodents. Both rats and mice can be used. To elicit working memory processes, the rodent must distinguish between a sample (familiar) light stimulus and a novel light stimulus after a delay. With a correct selection, the rodent will receive a food reward. A major benefit of TUNL compared to other similar tasks is the circumvention of spatial "mediating strategies" that the rodent may use to supplement or replace working memory processes to complete the task successfully. Each trial is 'unique', as the stimuli are pseudo‐randomized between trials in an array of spatial locations. The TUNL task uses a progression of six training steps to teach the rodent the associated rules necessary to complete the full task. Task performance is typically measured by trials completed and by accuracy. Task accuracy can be evaluated across various spatial separations to engage hippocampal‐dependent processes involved in spatial pattern separation. The latency between trial responses can also be evaluated, with food reward collection latency as a measure of motivation. The TUNL task can be used to assess working memory and cognitive deficits in rodent models with neurodegenerative and neurological disorders, providing a valuable tool to screen for new treatment options, in addition to assessing basic neurobiology. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Handling and habituation prior to training Basic Protocol 2 : Initial Touch Training Basic Protocol 3 : Must Touch Training Basic Protocol 4 : Must Initiate Training Basic Protocol 5 : Punish Incorrect Training Basic Protocol 6 : Initial TUNL Training Basic Protocol 7 : Full TUNL Training Support Protocol 1 : Using ABET II touch program Support Protocol 2 : Preparation of touchscreen chambers prior to training sessions